International Financial Statistics Yearbook, 2014. (International Financial Statistics; International Financial Statistics, 2014)
This chapter presents a report on International Financial Statistics (IFS). The country tables normally include data on a country's exchange rates, IMF position, international liquidity, monetary statistics, interest rates, prices, production, labor, international transactions, government accounts, national accounts, and population. Selected series, including data on Fund accounts, international reserves, and international trade, are drawn from the country tables and published in world tables as well. Exchange rates in IFS are classified into three broad categories, reflecting the role of the authorities in determining the rates and/or the multiplicity of the exchange rates in a country. In IFS, exchange rates are expressed in time series of national currency units per SDR (the unit of account for the IMF) and national currency units per US dollar, or vice versa. The country tables, euro area tables, and world tables provide measures of effective exchange rates, compiled by the IMF's Research Department, Strategy, Policy, and Review Department, Statistics Department, and area departments.